Tinta dan Tasbih : Jejak Intelektual Buya Hamka dan Syekh Nawawi Al-Bantani dalam Khazanah Keilmuan Nusantara - Ahmad Bludan Vija; Zhafira Ramadhani; Syahla Salsabila; Sabillah Aiska; Abdul Fadhil (Advances In Education Journal, 2025)
This article explores the integration of 'tinta' (intellectualism) and 'tasbih' (spirituality) in the thoughts of two Indonesian scholars, Sheikh Nawawi Al-Bantani and Buya Hamka. The primary challenge of this research is how these two figures successfully combined scientific rationality with spiritual depth in their works. This research aims to analyze this integration model and its relevance to the development of contemporary Islamic thought. The method employed is a literature study, which involves collecting data from primary works and related academic studies. The results show that Sheikh Nawawi represents an intellectual sufi integration oriented towards preserving classical traditions. At the same, Buya Hamka presents an integration that is modern, active, and responsive to social dynamics. These findings strengthen the paradigm that knowledge and spirituality are inseparable. In conclusion, the models of these two scholars can serve as important references for contemporary Muslims.